Study of biochar on growth and yield of Choy Sum (Brassica chinensis L.var parachinensis) - Chittawanij, A.; Marubodee, R.; Pornsuriya, P. (International Journal of Agricultural Technology, 2022)
The effect of biochar on the growth and yield of choy sum was investigated at harvesting time for 7 weeks after sowing in a pot experiment. The effect of biochar on the growth and yield of vegetables and the effects of biochar on the physiochemical properties of the soil were recorded. The results revealed that using wood biochar at the ratio of 4 t h −1 significantly increased height, width leaves, number of leaves, chlorophyll content, fresh and dry weight of the plant compared to the control treatment. In term of soil properties, biochar application in soil increased soil pH, while electrical conductivity (EC) was not altered. Thus, addition biochar to the soil can be one of the best practices to overcome any biotic stress in soil and increased the crop productivity